ETHNOPHYSICAL INTEGRATION IN COOPERATIVE LEARNING BASED ON BATAK CULTURE TO IMPROVE GENERIC SKILLS OF SCIENCE (GSS) AND STUDENT TEAMWORK - Naimah Hasanah; Sahyar Sahyar; Derlina Derlina (Jurnal Pendidikan Fisika, 2021)
This study aims to improve the generic science skills and teamwork of students through cooperative learning models based on Batak culture with the Culturally Responsive Teaching approach. This research was conducted at the MAS Medan UIN SU Laboratory T.P 2018/2019. This type of research is a quasi-experimental exercise using two group pretest-posttest design. The instruments used were generic science skills test instruments and student collaboration questionnaires. Data were analyzed using SPSS 16.0, t test and gain test. The results showed that the generic science skills and teamwork of students who were taught by cooperative learning models based on Batak culture were better than those taught by conventional models. Physics learning through the Culturally Responsive Teaching approach integrated with ethnophysics can increase KGS and student collaboration including; direct observation, the law of cause and effect, logical inference, ability to participate, sharing ability and communication skills.